The Modification of Muslim Women’s Hijab to Meet Modern Life Styles in a Western Society - Maqsood,Elham; Cluver,Brigitte; Chen,Hsiou-Lien (International Textile and Apparel Association, 2016)
Women residing in non‑Muslim countries have indicated that they have experienced negative feedback from others due to their use of the hijab (Ruby, 2006; El-Ghobashy, 2011). The impact of Muslim women’s experiences on their use of the hijab has received little attention from researchers (Tarlo, 2010). Therefore, the purpose of this research was to investigate why and how a group of Muslim women developed and adopted a variation of the hijab, the Multipurpose Modern Hijab (MMH), to wear while living in the United States. Results show that participants developed a hijab alternative that they believe retains its ability to communicate their religious beliefs and commitment to Allah, but also is easier to put on and keep on, more comfortable, and more accepted by the non-Muslim community. One major challenge participants noted is finding a single fabric that meets their needs in terms of aesthetics and comfort; there is a need for fabrics that are designed specially for hijab users.
Keywords: Design Program